12= -12
-1/2= 1/2
.25 =-.25
-27=27
0=0
Answer:
(3, 0) and (5, 0)
Step-by-step explanation:
we have
![y=x^{2}-8x+15](https://tex.z-dn.net/?f=y%3Dx%5E%7B2%7D-8x%2B15)
we know that
The x-intercepts are the values of x when the value of y is equal to zero
so
For y=0
![x^{2}-8x+15=0](https://tex.z-dn.net/?f=x%5E%7B2%7D-8x%2B15%3D0)
The formula to solve a quadratic equation of the form
is equal to
![x=\frac{-b\pm\sqrt{b^{2}-4ac}} {2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%7D%20%7B2a%7D)
in this problem we have
so
![a=1\\b=-8\\c=15](https://tex.z-dn.net/?f=a%3D1%5C%5Cb%3D-8%5C%5Cc%3D15)
substitute in the formula
![x=\frac{-(-8)\pm\sqrt{-8^{2}-4(1)(15)}} {2(1)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-8%29%5Cpm%5Csqrt%7B-8%5E%7B2%7D-4%281%29%2815%29%7D%7D%20%7B2%281%29%7D)
![x=\frac{8\pm\sqrt{4}} {2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B8%5Cpm%5Csqrt%7B4%7D%7D%20%7B2%7D)
![x=\frac{8\pm2} {2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B8%5Cpm2%7D%20%7B2%7D)
![x=\frac{8+2} {2}=5](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B8%2B2%7D%20%7B2%7D%3D5)
![x=\frac{8-2} {2}=3](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B8-2%7D%20%7B2%7D%3D3)
so
x=3, x=5
therefore
The x-intercepts are (3,0) and (5,0)
Answer:
B. y = -2/3x + 12
Step-by-step explanation:
Formula to find the slope when given two points on a line:
<u>y</u><u>2</u><u> </u><u>-</u><u> </u><u>y</u><u>1</u>
x2 - x1
Substitute the two given points (6, 8) (9, 6):
<u>6</u><u> </u><u>-</u><u> </u><u>8</u>
9 - 6
Slope = -2/3x
We found the slope! And the answer choices already gave us one y-intercept, which is 12. The last thing we do is we form an equation with the information we solved and that was given to us.
y = slope (x) + y-intercept
y = -2/3x + 12
The answer choice that matches this equation is B.
In conclusion, the equation that best estimates the line of best fit shown above is answer choice B.
Answer:
The correct option is;
Use a scale factor of 2
Step-by-step explanation:
The parameters given are;
A = (1, -6)
B = (5, -6)
C = (6, -2)
D = (0, -2)
A'' = (1.5, 4)
B'' = (3.5, 4)
C'' = (4, 2)
D'' = ( 1, 2)
We note that the length of side AB in polygon ABCD = √((5 -1)² + (-6 - (-6))²) = 4
The length of side A''B'' in polygon A''B''C''D'' = √((3.5 -1.5)² + (4 - 4)²) = 2
Which gives;
AB/A''B'' = 4/2 = 2
Similarly;
The length of side BC in polygon ABCD = √((6 -5)² + (-2 - (-6))²) = √17
The length of side B''C'' in polygon A''B''C''D'' = √((4 -3.5)² + (2 - 4)²) = (√17)/2
Also we have;
The length of side CD in polygon ABCD = √((6 -0)² + (-2 - (-2))²) = 6
The length of side C''D'' in polygon A''B''C''D'' = √((4 -1)² + (2 - 2)²) = 3
For the side DA and D''A'', we have;
The length of side DA in polygon ABCD = √((1 -0)² + (-6 - (-2))²) = √17
The length of side D''A'' in polygon A''B''C''D'' = √((1.5 -1)² + (4 - 2)²) = (√17)/2
Therefore the Polygon A B C D can be obtained from polygon A''B''C''D'' by multiplying each side of polygon A''B''C''D'' by 2
The correct option is therefore;
Use a scale factor of 2.